Kebutuhan Air Harian Masyarakat Desa Jada Bahrin Kabupaten Bangka - Endang Setyawati Hisyam; Ferra Fahriani; Rahmad Hidayat (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
Jada Bahrin village produces vegetables, rubber, pepper, and pineapple. The people in this village work as a farmer, fisherman, trader, and entrepreneur. They face a big problem to get water in dry season. They only rely on artificial pond to collect and distribute the water to the people. The goals of this study is to know the average daily water demand at present and the prediction of water needs for the next 10 years as well as the factors that influence the water needs in Jada Bahrin. Data for analysis were gathered by distributing questionnaires to respondents. Based on the analysis, the average daily water demand of each person in Jada Bahrin Village was 107.83 liters/person/day (Ipoph) and the prediction of the total water needs of Jada Bahrin Village in the next 10 years (2028) was 2.43 liters/second. Factors affecting the need for clean water were the type of work, the level of income and the influence of climate